ANALISIS MOTIVASI PEMUDA DALAM BERTANI KAKAO - Elen Oktavia; Unang Mulkhan (Jurnal Perspektif Bisnis, 2019)
Drawing upon Scott’s theory (1987) on the moral economy of the peasant and Popkin’s theory (1986) on the rational peasant, this research aims to reveal the relationships of 5 different variables: subsistence economy, subsistence ethics, risk distribution, moral economy, and political economy, on young people’s motivation in cocoa’s farming. This study employed quantitative approach, using a simple random sampling technique with surveys of a hundred of young people in Way Ratai district of Pesawaran Lampung. The area of the district is mostly covered by cocoa plantation where many national and multi-national companies on cocoa and chocolate productions buy cocoa beans from the area. Findings show that two variables provide positive and significant effects, namely, the distribution of risk and moral economy. Moreover, traditional economic systems and kinship are still dominated in everyday life of cocoa farmers. For the variable of political economy, there is also a positive effect but it is not significant. Further findings found that two variables: subsistence economic and subsistence ethics, do not have positive and significant effects on young people’s motivation in growing cocoa. Thus, this study argues that subsistence economic and subsistence ethics are not relevant anymore for young people to grow cocoa commodity.